The legislative confrontation of the crime of benefiting public money in Iraq -A comparative study- - جاسم, زياد ناظم (Journal of Legal Sciences, 2019)
The legislator sought to provide the greatest protection for public funds. The wisdom of this is clear and is one of the necessities of running the public utilities regularly and steadily. The waste of public money and its lack of public facilities impede the provision of its services and the delay of services and hindering access to the public. In Iraq, services are lagging behind and almost a collapse in service. Hence, the legislator has created a special protection for the employees because of the importance of the role played by this group as they represent the state with all its institutions and to enable them to perform their duties. To make the acts committed against them in the performance of their duties or to cause them to be grounds for aggravating punishment. On the other hand, the legislator considered that the employee's use of public money was a crime of aggravating circumstances, in breach of the Covenant of the Secretariat vis-à-vis the General Facility and the State in general